1984
DOI: 10.1073/pnas.81.14.4534
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of an amplified c-myb oncogene in two cell lines from a colon carcinoma.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 31 publications
4
66
0
Order By: Relevance
“…Data associating c-myb gene ampli®cation with colon carcinomas and adenomatous polyps has been con¯icting (Yokata et al, 1986;Meltzer et al, 1987;Torelli et al, 1987;Grego et al, 1994). However, studies examining colon tumour cell lines have consistently reported a very low incidence of c-myb gene ampli®cation (Alitalo et al, 1984;Melani et al, 1991;Trainer et al, 1988). The data presented in this study supports these ®ndings as there was no evidence of ampli®cation in any of the seven human colon tumour cell lines examined.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Data associating c-myb gene ampli®cation with colon carcinomas and adenomatous polyps has been con¯icting (Yokata et al, 1986;Meltzer et al, 1987;Torelli et al, 1987;Grego et al, 1994). However, studies examining colon tumour cell lines have consistently reported a very low incidence of c-myb gene ampli®cation (Alitalo et al, 1984;Melani et al, 1991;Trainer et al, 1988). The data presented in this study supports these ®ndings as there was no evidence of ampli®cation in any of the seven human colon tumour cell lines examined.…”
Section: Discussionsupporting
confidence: 80%
“…In the colonic system, c-myb expression is observed in normal murine and human colonic mucosa and is present at elevated levels in human pre-malignant adenomatous polyps, tumours and tumour cell lines (Alitalo et al, 1984;Torelli et al, 1987;Trainer et al, 1988;Ramsay et al, 1992;Thompson and Ramsay, 1995). In contrast to c-myb expression in transformed hemopoietic tissues and cells of murine and avian origin, there was no evidence of Myb protein truncation (Ramsay et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Since high levels of c-Myb are present in many cancers, including leukemias, colon cancer, neuroblastoma, breast cancer, and lung carcinoma (Alitalo et al 1984;Gri n and Baylin, 1985;Thiele et al, 1988;Guerin et al, 1990), understanding the mechanisms underlying Tax-mediated c-Myb repression may reveal new targets for the treatment of these diseases.…”
Section: C-myb Promoter Transrepression By Tax Is Independent Of Its mentioning
confidence: 99%
“…In human tumors, very few chromosomal abnormalities resulting in the ampli®cation or mutation of cmyb have been described (Alitalo et al, 1984;Jacobs et al, 1994;Pelicci et al, 1984), and the c-myb locus does not feature in any of the chromosomal translocations occurring in human hematopoietic neoplasms (reviewed in Sanchez-Garcia, 1997). However, c-myb is frequently over-expressed in human myeloid and lymphoid leukemias.…”
mentioning
confidence: 99%